Some Aspects of the Condition of Poverty in the Holy Scripture - Jerí Tafúr, Alfredo (2019)
This paper is an academic reflection of a subjet that is related of the salvation and that has to do strictly with Christian praxis. To write about some aspects of the condition of poverty in Sacred Scripture is to mention a way of proceeding on the part of the one who believes, as well as a clear option made by God for the most vulnerable. The theological reflection will lead us to conclude that poverty is not wanted by God and that the poor and their condition of poverty will always be a solidary task for the believer, and an endless struggle of our people for social justice.